Dentinal defect formation during root canal preparation by Trunatomy files with and without the glide path - Lucas Rodrigues; Carlos Eduardo da Silveira Bueno; Alexandre Sigrist De Martin; Carolina Stringheta; Carlos Eduardo Fontana; Rina Andrea Pelegrine; Ana Grasiela da Silva Limoeiro; Wayne Martins Nascimento; Marilia Fagury Videira Marceliano-Alves; Daniel Guimarães Pedro Rocha (Faculdade São Leopoldo Mandic, 2024)
ABSTRACT Objective: The aim of the present study is to evaluate the occurrence of dentinal defects on the apical surface after rotary instrumentation at different working lengths with Trunatomy Prime system, with or without the use of a glide path file. Methods: Twenty human single-rooted mandibular premolars were selected and divided into 2 experimental groups (n=10). GTP group (Glide Path + Trunatomy Prime), the TP group (Trunatomy Prime). Results: To check the agreement between the examiners, the Kappa test was performed. Subsequently, the results were subjected to the Shapiro-Wilk normality test. The sample showed abnormal behavior and were subjected to the non-parametric Mann Whitney test with a significance level of 5%. No significant difference was found between the groups. Conclusion: It is concluded that there was no causal relationship with the formation of dentin defects with and without the use of glide path files at different limits of instrumentation with Trunatomy files.